Macroeconomic policies and food security - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2015)
The links between trade and food security have been debated for decades, with strong views covering a whole range of opinions: from those who argue that trade and trade openness cause hunger (Madeley, J., 2000) to others who believe that a complete liberalization of global agricultural trade is the best possible approach for food security (see, for instance, Gris-wold, 1999). There have been comprehensive reviews of case studies analyzing the links between trade and food security (see, for instance, FAO, 2003; H. Thomas (ed), 2006; McCorriston S., et al, 2013), but this systematic review of evidence does not seem to have abated the controversy (see Díaz-Bonilla (2015b) for an analysis of the debates and disagreements).